The impact of business intelligence on the marketing with emphasis on cooperative learning: Case-study on the insurance companies - Huang, Z.-X. (Elsevier Ltd, 2022)
Business Intelligence involves the strategies and technologies employed by businesses for the data analysis of business information. This study investigates the impact of Business Intelligence on the Marketing with emphasis on cooperative Learning. Descriptive-survey research method and field study were employed. 186 samples of employees from insurance companies are statistical population. The face validity and the experts' opinions were employed to determine the validity of the questionnaire for data investigating. Cronbach's alpha and Composite reliability were employed to appraised the accuracy of questions. The methods employed in descriptive statistics as Absolute Frequency Distribution tables, are mean for confirmatory factor. The results revealed that Business Intelligence has a certain and critical impact on marketing through cooperative Learning (Value of Statistics was greater than 1.96), Financial Performance (VoS was greater than 2.57), and Customer Behavior (VoS was greater than 2.57). Also, Business Intelligence teams have a certain and critical impact on Financial Performance (VoS was greater than 2.57), and Customer Behavior (VoS was greater than 2.57). Despite, Business Intelligence does not have a notable impact on Marketing (VoS was less than 1.64). Â© 2021 Elsevier Ltd